2021
DOI: 10.1002/pbc.29186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of universal health coverage on childhood cancer outcomes in Indonesia

Abstract: Background: Starting from 2014, the Indonesian government has implemented Universal Health Coverage (UHC) with the aim to make healthcare services accessible and affordable to all Indonesian citizens. A major reason for childhood cancer treatment failure in low-and middle-income countries, particularly among families with low socioeconomic status (SES), is abandonment of expensive cancer treatment. Our study compared childhood cancer treatment outcomes of the overall, low, and high SES population before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…For example, an observational study in Indonesia looked at a set of key health indicators, including maternal mortality ratio, infant mortality rate, and life expectancy, and found that UHC interventions achieved preliminary success in improving health equity and service access [ 7 ]. Another study from Indonesia used survival analysis to examine child cancer outcomes under UHC and reported significant improvements—especially among disadvantaged socioeconomic groups—in cancer survival and treatment failure [ 8 ]. However, the presence of multiple context-dependent confounders limited the generalizability of these findings to other similar healthcare settings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an observational study in Indonesia looked at a set of key health indicators, including maternal mortality ratio, infant mortality rate, and life expectancy, and found that UHC interventions achieved preliminary success in improving health equity and service access [ 7 ]. Another study from Indonesia used survival analysis to examine child cancer outcomes under UHC and reported significant improvements—especially among disadvantaged socioeconomic groups—in cancer survival and treatment failure [ 8 ]. However, the presence of multiple context-dependent confounders limited the generalizability of these findings to other similar healthcare settings.…”
Section: Introductionmentioning
confidence: 99%
“…Some of ALL2013 patients and all ALL2016 patients also benefited from the National Obligatory Health Insurance starting in 2014, especially patients from low SES. Based on our recent study, after starting of the new health insurance treatment abandonment in the low SES population decreased from 36% to 19% ( p < .001) 24 . In our setting, the uncertainties about disease prognosis, treatment‐related risks, financial burden, disease‐related communication, and the use of traditional medication emphasize the need for psychosocial care and assistance for families with a child with leukemia 25…”
Section: Discussionmentioning
confidence: 81%
“…Based on our recent study, after starting of the new health insurance treatment abandonment in the low SES population decreased from 36% to 19% (p < .001). 24 In our setting, the uncertainties about disease prognosis, treatment-related risks, finan-cial burden, disease-related communication, and the use of traditional medication emphasize the need for psychosocial care and assistance for families with a child with leukemia. 25 Similar with other studies in LMICs, 3,4,9,[26][27][28][29] infection was the major cause of death apart from relapse, both in ALL2013 and ALL2016.…”
Section: Discussionmentioning
confidence: 99%
“…The hospital serves population of 5.8 million in southern‐Java. Annually 180 children are diagnosed and treated for malignancies by 5 pediatric‐oncologists and 28 nurses 1 …”
Section: Methodsmentioning
confidence: 99%